Weed control and resistance of cotton cultivars to the herbicides diuron and fluometuron - Nóbrega, Laudemiro Baldoíno da; Beltrão, Napoleão Esberard de Macêdo; Azevedo, Demóstenes Marcos Pedrosa de (Pesquisa Agropecuaria Brasileira, 2014)
Two experiments (one with diuron and other with fluometuron) were conducted in a sand-loam soil in the Campo Experimental de Surubim (Surubim experiment field station) located in Surubim. Pernambuco, Brazil. The herbicides were applied in pre-emergence in the following rates: 0,7, 1,4 and 2,1 kg a.i./ha of diuron and 0.8, 1.6 and 2.4 kg a.i./ha of fluometuron, in four upland cotton cultivars (Gossypium hirsutum v. latifolium Hutch). The soils were fertilized with a 30-40-10 NPK formula with the objective of minimizing the effect of the variability of the soil fertility. The experimental area had a balanced population of broad and narrow-leave weeds. The results showed that the cultivars tested were resistant to the rate used of both herbicides and showed a similar competitive behavior in relation to the weeds. For the herbicide diuron one application of 0.7 and 1.4 kg a.i./ha was sufficient for an effective control with no toxic effect to the cotton plant. For the herbicide fluometuron the recommended rate is 2.2 kg a.i./ha.